Peran Inovasi dalam Meningkatkan Daya Saing Usaha Mikro Kecil dan Menengah (UMKM) di Kota Medan - Anju Andini; Eka Kristina Waruwu; Yusuf Adzka Tarigan (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the role of innovation in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. The research employs a qualitative approach through direct interviews with several MSME owners from various business sectors. The results reveal that innovation plays a significant role in strengthening business competitiveness through product development, digital marketing strategies, and improvements in production processes. Product innovation among MSMEs includes changes in design, quality enhancement, and product diversification based on market demand. Meanwhile, marketing innovation is achieved through the utilization of social media and digital platforms to expand market reach and improve customer engagement. However, MSME actors still face challenges such as limited capital, low digital literacy, and lack of access to training and mentorship. Therefore, collaboration between business actors, government, and supporting institutions is essential to build a sustainable innovation ecosystem that strengthens the competitiveness of MSMEs in the digital era.